UNDERSTANDING FACTORS OF USING PUBLIC TRANSPORTATION AMONG WOMEN IN KUALA LUMPUR - Yong Adilah Shamsul Harumain; Nikmatul Adha Nordin; S M Zaid; Hong Ching Goh; A Woodcock; D Mcdonagh; Muhammad Ahmad Al-Rashid; Komal Faiz (Jurnal Pengembangan Kota, 2020)
In recent decades, the percentage of women working outside their homes has ascended in many developing countries depicts the needs on the understanding of how women travel daily. Many claims, public transportation facilities, and infrastructure related to it do not consider the needs of women travelers but fit men's standards. As a result, many face difficulties became dependent on men for traveling or facing safety-related issues that deter them to use public transportation independently. Thus, this study is to identify factors of public transportation usage among women users in Kuala Lumpur. The study has able to identify three main attributes in public transportation usage factors that influence women users. Using the Structural Equation Modelling (SEM) researchers have found that situational attributes have a larger influence on public transportation frequency, in the use of public transportation and surrounding condition of the public transportation in the mode choice decisions of their travel preferences.